MacIntyre's After Virtue at 40 - Angier, Tom 1970- (Cambridge University Press, 2023)
Since its publication in 1981, Alasdair MacIntyre's After Virtue has been recognised as a classic. Primarily a work of moral philosophy, it also draws on sociology, classics, political science and theology to effect a unique intellectual synthesis, and its combination of erudition and challenging, even provocative argument has made a significant impact throughout the humanities disciplines. This volume of new essays unpacks the influence of After Virtue on ethical and political theory, sociology and theology, and offers a multi-faceted exploration of its significance. The essays offer a way into MacIntyre's philosophy, and demonstrate how, rather than waning in influence over the past forty years, his most seminal text has found an ever-wider audience and continues to inspire controversy and debate in the humanities